Improving the Productivity and Quality of Grafted Tomato Fruits under Salinity Stress Conditions (Damascus University Journal of agriculture sciences, 2021)
The research was carried out at the Bostan Al-Basha station Lattakia in Sulaiman Agricultural company, during September 2019. The hybrid "Neenar" was grafted on each rootstock "Defenser" and "XR400". The hybrid and grafted plants were grown in the greenhouse. Three levels of salinity (0, 50, 100 mg.L-1 of pure NaCl) were applied. Results showed that salinity led to a significant increase in the osmotic pressure and Na+ and Cl- content, increase of fruit total acidity, TSS, lycopene, carotenes, and a decrease of fruit firmness. Grafting on XR400 rootstock caused a decrease in the osmotic pressure (-0.85 MPa), and Na+ and Cl- contents, but caused an increase fruit total acidity (0.25%), TSS (3.04%), carotenes (1.64 mg.kg-1), and lycopene (0.83 mg.kg-1), without any effect on fruit firmness. Grafting on Defenser rootstock decreased osmotic pressure (-0.85 MPa), and Na and Cl contents, but led to an increase in the fruit firmness (1.17 kg.cm-2), and carotenes (1.24 mg.kg-1), without any effect on other indicators. Despite of productivity decreasing with increasing of salinity concentration, grafting on both rootstocks contributed in productivity increase (31.6, 30.97 kg.m-2 respectively).
Keywords: Tomato; Grafting; Salinity; Defenser rootstock; XR400 rootstock